Razvojni položaj Gorenjske statistične regije - Kušar, Simon (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2014)
The aim of the article is to define the regional structure by the system of selected indicators, which were applied for the evaluation of the relative developmental condition of Gorenjska statistical region in Slovenia. Methodological approach (standardization, ranking) as one of the elements of possible evaluation of regional development potentials was applied for the evaluation of comparative regional opportunities within the context of regional development.
Keywords: družbena geografija; ekonomski razvoj; Gorenjska; human geography; regionalna ekonomija; regionalni razvoj; regionalno planiranje; Slovenia; Slovenija; Upper Carniola